1990
DOI: 10.1093/oxfordjournals.humrep.a137122
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization failure in IVF: why and what next?

Abstract: Among 297 couples who underwent 587 oocyte collection procedures, 95 (16%) total fertilization failures (FF) were observed. This frequency is similar in couples with either normal or only mildly deficient spermatozoa (16.2 and 13.7% respectively) but is almost doubled in cases of moderately and severely defective sperm (26.5%). However, this latter group accounts for only 19% of FF events. The fertilization rate per oocyte (FR) follows an inverse trend. FR was correlated with the final (i.e. after swim-up) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Though definitions of poor response vary with regard to number of oocytes retrieved, many studies have suggested that low responders have lower fertilization rates, pregnancy rates, and implantation rates after an IVF cycle [13,19]. Complete fertilization failure, which occurs in approximately 16% of IVF cycles, was significantly more frequent in cycles that resulted in 3 or fewer oocytes [14,20]. Though it has been suggested that 6-10 oocytes is the ideal quantity to optimize the number of embryos ultimately transferred [21], retrospective analyses of poor response cycles and subsequent fertilization and pregnancy rates suggest that embryo transfer is still possible in this patient population and cycles should not be cancelled [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though definitions of poor response vary with regard to number of oocytes retrieved, many studies have suggested that low responders have lower fertilization rates, pregnancy rates, and implantation rates after an IVF cycle [13,19]. Complete fertilization failure, which occurs in approximately 16% of IVF cycles, was significantly more frequent in cycles that resulted in 3 or fewer oocytes [14,20]. Though it has been suggested that 6-10 oocytes is the ideal quantity to optimize the number of embryos ultimately transferred [21], retrospective analyses of poor response cycles and subsequent fertilization and pregnancy rates suggest that embryo transfer is still possible in this patient population and cycles should not be cancelled [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…An association between lower number of retrieved oocytes and lower fertilization rates and IVF outcome has been described [12,13]. Additionally, fertilization failure is a common finding when less than 3 oocytes are retrieved [14] The high fertilization rates, small numbers of fertilization failures, and lack of apparent long term drawbacks make ICSI an appealing solution for IVF [15,16]. Hence, it has been proposed that ICSI could improve fertilization rates and the likelihood of successful embryo transfer when the number of recovered oocytes is low [17].…”
Section: Introductionmentioning
confidence: 99%
“…1 Fertilization rates strongly predict the outcome of the ART cycle. [75][76][77][78] In cases where TFF occurs, there is a 29% chance of it recurring. TFF happens in 5-16% of IVF cycles.…”
Section: Fertilization Failure Fertilization Failure Incidence and Immentioning
confidence: 99%
“…ICSI is usually used when the quantity or quality of motile sperm is poor and when fertilization failure has occurred in previous IVF cycles. However, normospermia is observed in 5-10 % cases that fail to fertilize and form a zygote [4,5]. Because this type of failure is difficult to predict, results for obtaining zygotes are better for ICSI than IVF.…”
Section: Introductionmentioning
confidence: 99%